Airflow resistivity measurement and sound absorption performance analysis of sound-absorb cotton. (August 2021) - Liu, Xuewen; Xiong, Xinzhong; Pang, Jinxiang; Wu, Liang; Zhang, Heavy
Abstract: Porous materials are widely used for noise control treatments. Sound-absorb cotton is commonly used in the transportation industry such as automobiles and airplanes because of its excellent sound absorption performance. In this paper, two typical acoustical models were used to evaluate the sound absorption coefficient of sound-absorb cotton. By comparing the measurement results with those of acoustical models, suitable model for sound-absorb cotton can be found. Physical parameters are measured and calculated by experimentally and inverse methods. Porosity and density are directly measured, while airflow resistivity is measured by changing boundary conditions between sample and container. Tortuosity and characteristic length are identified by using material acoustic parameters identification software, when samples considered as limp and rigid skeleton-type respectively. When all parameters of the samples are obtained, then the sound absorption coefficient of the sample can be simulated by material acoustic simulation software. This paper, also investigated the effect on sound absorption coefficient by airflow resistivity due to different boundary conditions. The conclusion of the theoretical model applicable to sound-absorb cotton can be drawn from the results obtained, also proved the best method of airflow resistivity measure.